Application of decoupling networks in deadbeat controller for high-frequency link inverter - Zainal, Salam, Dr.; Toh, Leong Soon; Mohd. Zulkifli, Ramli (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/